General geology and slake durability index for different lithology of rock at Kampung Renyok Jeli, Kelantan - Fatin Najwa Supi (2017)
Research was conducted around Kampung Renyok area which covered approximately 25km². The purpose of this study is to produce geological map at scale 1,25000, to determine slake durability index of rock and to relate slake durability index of rock with different weathering grade classification. The study area composed of rock from granite, gneiss, metasedimentary, limestone and sandstone. Every type of rocks, igneous, metamorphic, sedimentary have different strength and its own durability. The durability of rocks depends on degree of weathering that changes the texture and mineralogy content of rock. Sensitivity of rock types against weathering can be determined by using durability parameter called as slake durability index that proposed by Franklin and Chandra (1972). Test was conducted with collecting 11 samples of granite and gneiss near Renyok waterfall area and 5 sample of sandstone near Felcra Reka area. The result of durability index from the test is used to determine durability classification and identify weathering grades. From the laboratory test, the range index durability value for granite samples is 98.11% to 99.05% in grades II, for gneiss samples 98.53% to 99.18% also in grades II, and for sandstone samples is 96.06% to 98.97% in grades II and 87.56% to 94.90% in grades III. It conclude that low value durability of rock caused the weathering grades increased. From the result obtained, granite and gneiss have almost same durability index value but different in texture and mineralogy content. For sandstone, it composed of different durability index value that are caused from its texture condition which nearly weathered during collecting the sample.